Pengamanan Data Transmisi Aplikasi Web Menggunakan Algoritma Kriptografi RSA: Studi Kasus dan Analisis - Hermalia Putri; Lurya Virna; Tia Febrianti; Tata Sutabri (Jurnal Manajemen Informatika & Teknologi, 2025)
In the rapidly developing digital era, web applications have become the main means of exchanging information, ranging from personal data, financial transactions, to business communications. However, the process of transmitting data over the internet network is very vulnerable to various security threats, such as eavesdropping, data tampering, and man-in-the-middle attacks. Therefore, a security mechanism is needed that can guarantee the confidentiality, integrity, and authentication of the data sent. One method that is widely used to secure data transmission is cryptography. This study focuses on the use of the RSA (Rivest–Shamir–Adleman) asymmetric cryptography algorithm, which uses a pair of public and private keys in the data encryption and decryption process. RSA provides advantages in terms of key distribution and security based on the mathematical complexity of large prime number factorization. The case study was conducted on a simple web application in the form of a personal data entry form that is usually sent in plain text. In this implementation, data from the client side is encrypted using the RSA public key, then sent to the server, and decrypted using the private key to be stored in the database. The test results show that RSA is able to secure data well and prevent data from being read directly even if wiretapping occurs. In addition, an analysis of the algorithm's performance in terms of encryption and decryption speed for various data sizes was also carried out. Although effective in terms of security, the RSA algorithm has limitations in handling large data, which causes a significant decrease in performance. Therefore, RSA is more suitable for use in hybrid systems with symmetric algorithms such as AES to encrypt message contents. This study provides a practical overview of how RSA can be applied in the context of the modern web and an analysis of its advantages and limitations in real practice